REACTION-ENHANCED PERMEABILITY DURING SERPENTINITE DEHYDRATION - Tenthorey E.; Cox S.F. (My University, 2003)
Fluid mobilization during prograde metamorphic reactions is a poorly understood, yet crucial, phenomenon that has implications for a number of geologic problems. Here we present the first experiments to characterize permeability evolution during dehydration of a natural rock. Dehydration of serpentinite specimens resulted in the generation of pore space and the rapid development of an interconnected pore network. During breakdown of antigorite to olivine + talc + H2O, permeability increased rapidly by at least three orders of magnitude. In natural systems, such an increase in permeability would be transitory, because high confining stresses would rapidly eliminate the porosity generated during reaction. Such transitory, reaction-enhanced permeability of serpentinite provides a mechanism by which fluids can migrate and possibly facilitate subduction-zone seismicity and contribute to partial melting of the mantle wedge. The results presented also have implications regarding middle- to deep-crustal fluid flow.
Keywords: permeability; dehydration reactions; serpentinite; ﬂuid migration; subduction zones